Pathways to Refugee Protection for Women: Victims of Violence or Genuine Lesbians?. (1st July 2022) - Dustin, Moira
Abstract: Failures in UK decision-making for women seeking protection from gender-based violence vary depending on the claimant's (purported) sexuality. These failures are attributable, at least in part, to the application of the particular social group Refugee Convention ground which channels claims along two distinct pathways: one path, for women assumed to be straight, focuses on the violence that threatens them; in contrast, for lesbian and bisexual women, the focus is on their sexuality. In either case, the claimant's autonomy and individuality is eclipsed, but different stereotypes come into play depending on her (imputed) sexuality. This article argues that greater use of the political opinion Convention ground, and a holistic, rights-based approach would improve refugee status determination for all women, regardless of their sexuality.